Association Between Psychological Distress and Coping Styles in Family Caregivers of People with Intellectual Disability or Chronic Mental Disorder in Mongolia - Delgermaa Sendmaa; Namuun Ganbaatar; Orgilmaa Regzedmaa; Erdenetuul Nuden; Enkhtuul Chuluun; Sundui-Yanjmaa Luvsangenden; Gankhuyag Gochoosuren; Dolgorjav Myagmarjav; Oyungoo Badamdorj; Khishigsuren Zuunnast; Myagmartseren Dashtseren; Naranbaatar Nyam; et al. (Nursing Reports)
Around the world, family caregivers are an important source of support for people with intellectual disability (ID) and for those with severe mental disorder (SMD), although the level of support can be influenced by the culture and government healthcare systems in each country. However, there is little evidence about the mental health and coping mechanisms of these caregivers in low-income countries. To address this need, we aimed to elicit whether there are potential links between coping style, mental health, and perceived burden experienced by this group, using a sample from a central Asian upper middle-income country. Methods: We recruited 120 participants, of which 60 were caregivers of people with ID and 60 of people with SMD. All participants were recruited from Ulaanbaatar, the capital city of Mongolia, Central Asia, and were asked to complete of the Depression, Anxiety and Stress Scale (DASS) and the Coping Orientation to Problems Experienced inventory scale (COPE). Multiple regression analyses were used to investigate associations between these measures. Results: We found that DASS scores were significantly higher among the sample of caregivers of individuals with ID than in those of SMD. Mental and behavioral disorders were associated with higher DASS scores in the sample of caregivers of those with SMD. Good coping styles, indicated by higher scores in the COPE, were associated with increased age in caregivers of individuals with ID. Conclusion: Although overall the carers of people with SMD appeared to have better active coping skills and better acceptance of the caring role, they demonstrated comparatively high levels of stress. This study was not registered.